SOSIALISASI POTENSI ASTAXANTHIN DALAM MEMBANTU PENGENDALIAN TEKANAN DARAH DI UPTD PUSKESMAS LHOK BEURINGEN - Wasliati, Balqis; Kasim, Felix; Rambey, Harris; Rifai, Achmad (Yayasan Education and Social Center, 2024)
Hypertension is a significant public health issue and has shown a notable increase in prevalence in Indonesia in recent years. According to the 2018 Basic Health Research (RISKESDAS), the prevalence of hypertension in Indonesia reached 34.1%, up from 25.8% in 2013. The impact of hypertension is substantial, contributing to 45% of deaths from heart disease and 51% of deaths from stroke. Astaxanthin, a natural carotenoid antioxidant found in various aquatic organisms, has shown potential as a blood pressure regulator through various mechanisms. Research indicates that astaxanthin is effective in reducing blood pressure and improving cardiovascular health. This community service program aims to increase public knowledge about astaxanthin at UPTD Puskesmas Lhok Beuringen through socialization and lectures. The results of the activities showed an increase in understanding and interest in astaxanthin among the community, as well as indications of changes in health behavior. The village of Meunasah Beuringen has shown a commitment to continuing this health education program, hoping to become a successful example for other villages in improving public health through effective education